(3CMcGe cd heG Ydjg JOds - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3daXI cd EPG de JbY JGHYg aEeG Cf JVGa daXkG hEeGe Cf JLQO s
(3BNQgG (B:s
(3hbO PcQJ Pdc ai bhdg JYGdi (B( (3hLGAJ cd faS eYgG SGFb hTgjO (B) (3ai JaSjQi gPG eG JjSQ PcQg ai gPg GdeSFdI hGddg CYde hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B21s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs